การพัฒนากระบวนการนําครูใหม่เข้าสู่วิชาชีพโดยใช้แนวคิดการพัฒนาบทเรียนร่วมกันเป็นฐาน ร่วมกับการเป็นพี่เลี้ยงเพื่อเสริมสร้างความสามารถในการออกแบบการเรียนการสอน - ฐิติจำเริญพร เกรียง; ตรีวรัญญู ชาริณี; สุวรรณมรรคา สิริพันธุ์ (Journal of Education Studies, Chulalongkorn University, 2019)
This research aimed to develop the induction process based on lesson study approach with mentoring and investigated results from implementing the developed induction process on novice teachers. The case studies include eight primary and secondary teachers who did not graduate from any educational program. Participants were selected through a purposive sampling method. The quantitative data collection instruments included: lesson plan evaluation form, teaching evaluation form, and analyzing and redesigning lesson plan evaluation form. The qualitative data has been collected from participants’ interviews, classroom observations, participants’ reﬂections and observation sharing. The statistics used in the data analysis include percentage, mean, and content analysis. The research ﬁndings suggested that the developed induction process was composed of three steps which were; Step (1) team-building and goal-setting, Step (2) in - class instructional design learning, and Step (3) professional sharing and learning in instruction as well as instructional design. This developed induction process enhanced novice teachers’ ability in designing instruction continuously, in designing learning activities that make their students achieve the learning objectives and more engage in classrooms activities, in selecting teaching materials that suit their students’ learning, in designing different assessment and evaluation methods including classroom management that facilitates teaching instruction.